Penerapan Metode Simple Additive Weighting Pada Sistem Pemilihan PLP/Laboran Berprestasi Politeknik Negeri Bengkalis - Lilik Hidayati; Lidya Wati (Lembaga Pengembangan Kinerja Dosen, 2025)
The selection of outstanding PLP/Laboran at Politeknik Negeri Bengkalis is an effort to appreciate the contributions of educational staff in supporting academic and non-academic activities. However, the manual selection process faces challenges such as taking a long time and being inefficient. To simplify and improve the accuracy of the selection process, a web-based Decision Support System is needed to assist the committee and judges in selecting outstanding laborans. This system uses the Simple Additive Weighting (SAW) method with weights assigned to each criterion, namely education, self-description, and outstanding achievements. The implementation of the SAW method in this system results in ranking laborans, which helps determine the winner. Based on testing with five field data, the system shows an accuracy of 100%. The software development method used is the Rational Unified Process (RUP), which emphasizes step-by-step system development with a focus on user needs at each stage. The implementation of RUP shows that this system is easy to use, meets user needs, and helps the selection process run more smoothly.